86 Haemorrhagic Stroke: What's in a Bleed?. (16th September 2019) - Noone, Imelda; Kate Meagher, Mary; Davey, Naomi; O'Shea, Diarmuid; Cassidy, Tim
Abstract: Background: Intracerebral haemorrhage (ICH) accounts for approximately 20% of all strokes and is a leading cause of disability and mortality. The distribution of the ICH(Lobar v Deep) may be explained by the two major aetiologies of ICH, Cerebral Amyloid Angiopathy (CAA) versus hypertensive (HBP) respectively. The aim of our study was to look at outcomes of lobar versus deep ICH stroke patients. Methods: We analyzed data of all ICH's admitted in 2018 using SPSS. Demography, classification of haemorrhage, hypertension, atrial fibrillation (AF) and anticoagulation history, pre and post stroke Rankin and subsequent outcome were analyzed. Results: 373 acute strokes were admitted of which 66(18%) were ICH. Mean age was 73yrs (52-93) and 50% were male. On neuroradiology imaging, 40(60%) were lobar and 26(39%) were deep. Lobar haemorrhages were significantly more likely to be older (p = 0.0001) however, there was no significant difference in pre-stroke Rankin. Post stroke the lobar haemorrhages had both a worse outcome from disability (p = 0.005) and mortality (p = 0.0001). 17(26%) patients with a ICH also had AF with 94% were on an oral anticoagulant(OAC).17.5% of the lobar bleeds were on an OAC versus 36% of the deep ICH. Of the lobar bleeds on OAC none died versus 4 of the deep ICH (p = .001). In total, 48(72%) of patients had a history of hypertension, but only 34(51%) were on HBP medication on admission. Conclusion: There were a greater proportion of patients with lobar versus deep bleeds in our cohort which may be due to the older population in our area. Mortality and disability was far greater in the lobar cohort. None of the lobar bleeds with AF who were on OAC died in contrast to the deep ICH patients. This may suggest that more aggressive hypertensive treatment is required in this subpopulation.